Cellulose acetate-poly{[9,9-bis(6′-N,N,N-trimethylammonium)hexyl]fluorene-phenylene} bromide blends: Preparation, characterization and transport properties - Cerqueira, D. (2012)
Texto completo: acesso restrito. p. 420–426